Melanoma risk‐takers: fathers and sons. (February 2015) - Eisinger, F.; Morère, J.‐F.; Pivot, X.; Grange, F.; Lhomel, C.; Mortier, L.; Robert, C.; Saiag, P.; Sassolas, B.; Viguier, J.
Abstract: Objectives: The incidence of skin cancers, melanoma in particular, is increasing rapidly. Consequently, specific recommendations for sun‐protection measures now exist. This survey set out to assess the compliance of the general population with these guidelines. Methods: The French nationwide observational survey, EDIFICE Melanoma, was conducted (28 September to 20 October 2011) through phone interviews of a representative sample of 1502 subjects aged ≥ 18 years, using the quota method. Sun‐protection was defined as frequent or systematic use of clothes or sunscreen. The group of individuals who declared exposure to the sun ( N  = 1172) was subdivided: risk‐takers ( N  = 442), and those who used sun protection ( N  = 730). Results: Risk‐takers were significantly more often male (62% vs. 44%, P  < 0.01), had a lower level of education (40% vs. 26%, P  < 0.01), lower incomes (2587 euros vs. 2948 euros/month) and were more often smokers (42% vs. 31%, P  < 0.01). In contrast, age, marital status and use of sunbeds were not significantly different between the two groups. Interestingly, risk‐takers had less risk factors for melanoma. However, they were less well‐informed about high‐risk exposure and optimal use of sunscreen. Sun‐protection measures for their children were less stringent than those of the group who used sun protection: systematic/frequent use of sunglasses (42% vs. 59%, P  < 0.01), systematic use of sunscreen (77% vs. 86%, P  < 0.01), and frequent renewal (69% vs. 82%, P  < 0.01), high sun protection factors (SPF) (46% vs. 56%, P  < 0.01), use of clothing (84% vs. 92%, P  < 0.01) and hats (88% vs. 94%, P  < 0.01). Conclusions: Risk‐takers are characterized by a lesser understanding of sun‐protection measures and behaviours. Their children benefit less from protective measures than those of people who use sun protection themselves. Improved understanding may well improve behaviours; one can therefore legitimately predict a considerable impact on parents' attitude to their own protection and that of their children.